2014
DOI: 10.3233/ies-140544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low to moderate intensity walking and cycling on glycaemic and metabolic control in type 1 diabetes mellitus adolescent males: A randomized controlled trial

Abstract: BACKGROUND: Type 1 diabetes mellitus (T1DM) is characterized by an autoimmune destruction of pancreatic beta cells, i.e., the immune system destroys the special cells that make and secrete insulin. OBJECTIVE: To evaluate the effect of 12 weeks exercise programme on glycaemic and metabolic control in T1DM adolescents. METHODS: Twenty-four T1DM adolescent males (12-16 y) were randomised into an exercise (n = 12) and control group (n = 12). Twelve weeks of exercise programme was administered to the exercise group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 23 publications
0
13
0
6
Order By: Relevance
“…The five remaining studies yielded relatively consistent results about glycemic control and PA. Regardless of type, duration, and frequency of the exercise, four studies (Gusso et al, 2012;Nguyen et al, 2015;Shin et al, 2014;Tomar et al, 2014) showed no significant associations between PA and HbA1c. In the fifth study by Carabott Pawley et al (2016), the results showed stabilized levels of HbA1c in the experimental group compared with a 0.6% increase in the control group after the exercise program; however, the results were statistically insignificant (p > .05).…”
Section: Results On Biochemical Outcomes In the Interventional Studiesmentioning
confidence: 94%
See 4 more Smart Citations
“…The five remaining studies yielded relatively consistent results about glycemic control and PA. Regardless of type, duration, and frequency of the exercise, four studies (Gusso et al, 2012;Nguyen et al, 2015;Shin et al, 2014;Tomar et al, 2014) showed no significant associations between PA and HbA1c. In the fifth study by Carabott Pawley et al (2016), the results showed stabilized levels of HbA1c in the experimental group compared with a 0.6% increase in the control group after the exercise program; however, the results were statistically insignificant (p > .05).…”
Section: Results On Biochemical Outcomes In the Interventional Studiesmentioning
confidence: 94%
“…The five remaining studies yielded relatively consistent results about glycemic control and PA. Regardless of type, duration, and frequency of the exercise, four studies (Gusso et al., ; Nguyen et al., ; Shin et al., ; Tomar et al., ) showed no significant associations between PA and HbA1c. In the fifth study by Carabott Pawley et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations